Community-level perceptions of drivers of change in nutrition: Evidence from South Asia and sub-Saharan Africa - Nisbett, Nicholas; van den Bold, Mara; Gillespie, Stuart; Menon, Purnima; Davis, Peter; Roopnaraine, Terence; Kampman, Halie; Kohli, Neha; Singh, Akriti; Warren, Andrea (Elsevier, 2017)
Changes in the immediate, underlying and basic determinants of nutritional status at the community- and household-level are a logical and empirical prerequisite to reducing high levels of undernutrition in high burden countries. This paper considers these factors directly from the perspective of community members and frontline workers interviewed in six countries in South Asia and sub-Saharan Africa. In each country, in-depth interviews were conducted with mothers, other community members and health workers to understand changes in health and nutrition practices, nutrition-specific interventions, underlying drivers and nutrition-sensitive interventions, and life conditions. Overall, the need for basic improvements in livelihood opportunities and infrastructure are solidly underscored. Nutrition-specific and -sensitive changes represented in most cases by deliberate government or NGO supported community interventions are rolling out at a mixed and uneven pace, but are having some significant impacts where solidly implemented. The synthesis presented here provides an invaluable source of information for understanding how community-level change occurred against a wider backdrop of national level progress.